Physical and chemical properties of orthodontic brackets after 12 and 24 months: in situ study - Bernardo de Azevedo Bahia MENDES; Ricardo Alberto Neto FERREIRA; Matheus Melo PITHON; Martinho Campolina Rebello HORTA; Dauro Douglas OLIVEIRA (University of São Paulo, 2014)
Objective: The aim of this article was to assess how intraoral biodegradation influenced the surface characteristics and friction levels of metallic brackets used during 12 and 24 months of orthodontic treatment and also to compare the static friction generated in these brackets with four different methods of the ligation of orthodontic wires. Material and Methods: Seventy premolar brackets as received from the manufacturer and 224 brackets that were used in previous orthodontic treatments were evaluated in this experiment. The surface morphology and the composition of the deposits found in the brackets were evaluated with rugosimetry, scanning electron microscopy, and energy dispersive X-ray spectroscopy. Friction was analyzed by applying tensile tests simulating sliding mechanics with a 0.019x0.025" steel wire. The static friction levels produced by the following ligation methods were evaluated: loosely attached steel ligature around all four bracket wings, steel ligature attached to only two wings, conventional elastomeric ligation around all 4 bracket wings, and non-conventional Slide® elastomeric ligature. Results: The results demonstrated the presence of biodegradation effects such as corrosion pits, plastic deformation, cracks, and material deposits. The main chemical elements found on these deposits were Carbon and Oxygen. The maximum friction produced by each ligation method changed according to the time of intraoral use. The steel ligature loosely attached to all four bracket wings produced the lowest friction levels in the new brackets. The conventional elastic ligatures generated the highest friction levels. The metallic brackets underwent significant degradation during orthodontic treatment, showing an increase in surface roughness and the deposit of chemical elements on the surface. Conclusion: The levels of static friction decreased with use. The non-conventional elastic ligatures were the best alternative to reduce friction.